The Perspective of Students with Various Anxiety Levels on the Elicitation Techniques in the EFL Classroom - Respati, Anggia; Kariadi, Mustasyfa Thabib; Roiyasa, Nisa (UM Purwokerto Press, 2025)
Students often experience anxiety in speaking and teachers have to think the right strategies to help students reduce their anxiety. Elicitation Techniques are used by the teachers to solve this problem, but some students still have difficulty in speaking. This study aimed to analyze the levels of speaking anxiety experienced by the students, the types of Elicitation Techniques used by the teacher and the students’ perceptions. This study used a descriptive-qualitative method with the grade VII C students at SMPN 10 Purwakarta as the participants. The data was obtained through observations, questionnaires, and interviews. Results showed three anxiety levels experienced by the VII C students; Very Anxious, Anxious and Mildly Anxious. Five students or 19.2% experienced anxiety on Very Anxious level, 15 (57.7%) students experienced Anxious level, and six students or 23.1% had a Mildly Anxious level. Regarding to the Elicitation Techniques, the teacher used five types of Elicitation Techniques, those are Asking Questions, Pictures to Ask Questions, Games/Activities to Ask Questions, Text/Dialogue to Ask Questions, and Non-Verbal Language to Ask Questions. The most frequently used types of Elicitation Techniques is Asking Questions with a total 70.2% or 40 times used, followed by Non-Verbal Language to Ask Questions 14%, and the third most frequently used types of Elicitation Techniques are Pictures and Text/Dialogue with a total 7%, and the type of Elicitation Techniques with the lowest percentage is Games/Activities with a total 1.8% or only one time used. Nine students with different anxiety levels that are interviewed in order to find out their perspective towards the Elicitation Techniques and most of the students with a total eight students with each different levels of anxiety feel more comfortable when the teacher asks questions using pictures and they feel uncomfortable when the teacher directly asks questions to elicits them to speak. Moreover, the students also admitted they want to be involved in activities such as games to make the learning session more interesting.